Engineering Geology of Diversion Tunnel Area at the Meninting Dam Construction, West Lombok, Province of West Nusa Tenggara, Indonesia - Yunie Wiyasri; Anastasia Dewi Titisari; Sia Pamela Dita; I Gde Budi Indrawan (Journal of Applied Geology, 2022)
The construction of Meninting Dam is undertaken to resolve the water needs in Meninting Watershed, West Lombok, Province of West Nusa Tenggara, Indonesia. Therefore, creating a diversion tunnel is imperative to avert the river flow as the dam project commences. Also, engineering geology work on the soil and rocks, including the classification of physical and mechanical properties were conducted in the intended tunnel site. These considerations were necessary because of the unavailability of rock identification data using the GSI (Geological Strength Index) method which used to design the portal slopes as a significant factor in tunnel safety. The results show the proposed area for diversion tunnel construction to be in the lithology of the polymict breccia and the lapilli tuff units, and the soil conditions were included in the SM category (silty sand). The level of surface rock weathering was divided into 3 units, including: highly weathered residual soil lapilli tuff, and highly, as well as moderately weathered polymict breccias. Meanwhile, 4 units were identified on the rock cores (subsurface) comprising highly weathered residual soil of lapilli tuff, and highly, moderately, and slightly weathered polymict breccias. Based on GSI (Geological Strength Index) of rock and surface data from the area of study, the rock quality was grouped as poor (GSI values: 21-40) to very poor (GSI values: 0-20). However, drilling data classified the mass quality subsurface rocks in fair (GSI values 41-55), poor (GSI values: 21-40), particularly in tunnels, and very poor (GSI values 0-20). Therefore, the rock mass quality is possibly used to design the slope of the tunnel portal as 45⁰-55⁰, in order to ensure safety.